HUBUNGAN TINGKAT PENGETAHUAN PASANGAN USIA SUBUR (PUS) DENGAN PERILAKU PEMILIHAN KB HORMONAL DI PUSKESMAS KARANGLEWAS - Retnowati, Misrina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Family Planning is one of the most basic and primary preventive health services. Knowledge of family planning acceptors about the effectiveness of contraceptives is needed so that family planning acceptors can choose the right contraception. This study aims to determine the relationship between the level of knowledge and behavior in hormonal family planning elections in the working area of Karanglewas Health Center. The results of this study can be input in order to increase the knowledge of fertile couples about hormonal birth control. The study was an observational study with a cross sectional approach. The population of this study were all PUS who visited the Karanglewas Health Center in the last three months (January - March 2018) as many as 585 people. Samples were taken by purposive sampling technique by drawing lots of 85 people. Data analysis method in this study used Chi Square test. The results of the study are known: 1) The knowledge of fetile age couples about Hormonal Family Planning mostly in the fairly good category as many as 51 people (60.00%), 2) Fertile age couples mostly chose Hormonal Family Planning as many as 45 people (52.94%), 3) There is a significant relationship between the level of knowledge about hormonal birth control and the selection behavior of Hormonal family planning (p= 0,000). The conclusion of the study is the level of knowledge related to the selection behavior of Hormonal Family Planning. Fertile Age Couples is expected to increase his knowledge, especially about contraception so that he can choose the most appropriate contraception.Keywords: Knowledge of Fertile Age Couples, Selection of Hormonal KB